Overview of alternative dispute resolution mechanisms (Revista de Investigaciones Universidad del Quindío, 2021)
Access to justice is a way to guarantee this human right to citizenship through its administration. In the Mexican state, Article 17 of the Constitution has a heterocompositive (trial) and autocompositive (negotiation, mediation, conciliation, arbitration) mechanism applicable in various matters and in accordance with its regulations. In this sense, it is important to consider the professionalization of the facilitators in charge of managing the conflict of mechanisms that require considering being applied from the principles of the same from the alternative justice. Although there is progress on the matter, this document exposes alternative justice based on alternative mechanisms in Mexico.
Keywords: Human right; facilitator; alternative justice; conflict resolution